O Ano, Ano, Ano, Ano? - Bautista, Martin C (Animo Repository, 2022)
Bautista, Martin C., Mendoza, Isabel Richell N., Ribaya, Hermes Sonny II P., O Ano, Ano, Ano, Ano?, Bachelor of Arts (Major in Communication Arts), January 2022, De La Salle University. O Ano, Ano, Ano, Ano is a 46-page production book for a short black comedy film about mental health deterioration caused by the COVID-19 pandemic. It centers on a minimum wage working student, Ivan, who gets stranded in his university condo after the lockdown. He is left alone in the confinement of his tiny unit for the next few months in struggle to find his way back home as begins to develop a hast abruption in his career, emotions, hearing, thoughts, and health. The project aims to debunk the shame towards seeking mental healthcare. The proponents aim to communicate a perspective of the issue from the minimum wage workers, expressing their experiences, beliefs and outlook towards it. They aim the project to be a platform that shall change people’s perception of mental health to be as important as their physical health. The visualization of the protagonist’s head growing larger as well as the increasing volume of background noise represents the buildup of his anxieties due to several factors in his environment. The project aims to portray the experience of mental health deterioration using the language of film. In creating the production plan, the proponents took into consideration the limitations of filming within the COVID protocols. The cast required on set was reduced to a single actor and the number of shooting days was limited to two. Furthermore, no additional crew members are needed and most of the technical equipment to be used would come from the proponents themselves. 46-page PDF document.